2017
DOI: 10.1186/s12917-017-1073-9
|View full text |Cite
|
Sign up to set email alerts
|

A diet change from dry food to beef induces reversible changes on the faecal microbiota in healthy, adult client-owned dogs

Abstract: BackgroundDiet has a major influence on the composition of the gut microbiota, whose importance for gut health and overall well-being is increasingly recognized. Knowledge is limited regarding health implications, including effects on the faecal microbiota, of feeding a diet with high content of red meat to dogs, despite some owners’ apparent preference to do so. The aim of this study was to evaluate how a diet change from commercial dry food to one with a high content of boiled minced beef and vice versa infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 82 publications
(123 reference statements)
6
83
3
Order By: Relevance
“…In another study (25), healthy dogs were switched to a diet consisting of kibble mixed with increasing percentages of minced beef meat. Due to the lack of formulation to meet nutritional requirements, combined with the short observation period (only 1 week for each combination), results need to be interpreted with caution.…”
Section: The Effect Of Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study (25), healthy dogs were switched to a diet consisting of kibble mixed with increasing percentages of minced beef meat. Due to the lack of formulation to meet nutritional requirements, combined with the short observation period (only 1 week for each combination), results need to be interpreted with caution.…”
Section: The Effect Of Dietmentioning
confidence: 99%
“…Interestingly, one of the Clostridiaceae strains was later identified as Clostridium hiranonis, a bacterial species associated with normal bile acid (BA) metabolism (25,26). A study (23) reported normal BA metabolism in healthy dogs fed BARF diets, with no significant difference from kibble-fed controls.…”
Section: The Effect Of Dietmentioning
confidence: 99%
“…Notably, the large intestine and faeces possess the highest density and diversity of bacteria, with Firmicutes, Bacteroidetes, Proteobacteria and Fusobacteria representing the prevalent bacterial phyla (Suchodolski, 2011). Like other mammals, the canine gut microbiota appears to be influenced by several factors, such as diet (Wu et al, 2016;Herstad et al, 2017;Kim et al, 2017), age (Masuoka et al, 2017), metabolic disorders including obesity and diabetes (Xu et al, 2016), as well as intestinal inflammatory diseases (Honneffer et al, 2014). However, these studies involved a small number of samples belonging to a single or just a few different breeds.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies involved a small number of samples belonging to a single or just a few different breeds. Like other mammals, the canine gut microbiota appears to be influenced by several factors, such as diet (Wu et al, 2016;Herstad et al, 2017;Kim et al, 2017), age (Masuoka et al, 2017), metabolic disorders including obesity and diabetes (Xu et al, 2016), as well as intestinal inflammatory diseases (Honneffer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, the development of microbial therapies with weight-loss applications in obese cats and dogs is challenging [7], in part due to the little we know about microbes and obesity [92,93] in these animal species and the wide inter-individual variation in the gut microbiome. This variation in the gut microbiome in pets is associated with the passing of time and aging [94][95][96][97][98], environmental factors, including diet [99], microbes in surrounding people [100], breed and other host genetics factors [101,102], clinical and subclinical conditions [91,93,103], gender [104], and behavior [105]. Here, we discuss the literature on feline and canine gut microbiota with regards to Verrucomicrobia-and Akkermansia-like 16S rRNA sequences (Table 1).…”
Section: The Feline and Canine Gut Microbiotamentioning
confidence: 99%